Can community notifications be improved to change public perceptions of released justice-involved persons and of the criminal justice system? - Himmen, Marguerite K. (International journal of law, crime and justice, 2023)
Community notifications are released by law enforcement to warn the public of a high-risk offender re-entering the community. Unfortunately, negative media attention generated from community notifications can impact an individual's ability to successfully reintegrate, leading to increased recidivism. This study examines whether modifications to community notifications can change public perceptions of offenders. Participants were presented with community notifications including jargon or simple language, an explanation of release or no explanation, and various sentence lengths served by the justice-involved individual. Notable results included a higher tolerance for justice-involved individuals when legal jargon was used in the explanation of release. Moreover, justice-involved people were perceived to be more likeable when information on sentence length was not provided. These findings contribute to a greater understanding of factors that affect public perceptions of justice-involved individuals. Addressing these factors could decrease recidivism rates by adequately informing the public of risks without negatively impacting offender reintegration.